Sustained monopolistic business relationships: A UK defence procurement case. - Humphries, Andrew; Wilding, Richard D. (Emerald Group Publishing Limited, 2004)
Business-to-business relationships within sustained monopolies, such as those within UK defence procurement, have received scant attention by management researchers. This is unusual because under these market circumstances there appear to be few incentives to achieve mutually beneficial outcomes despite their strategic policy importance. This paper argues that an understanding of the monopolistic environment using a transaction cost economics theoretical framework and relationship marketing concepts provides an approach to solving this problem as well as testing aspects of these disciplines empirically in a novel area. This plan is supported by the results from a pilot study and the paper concludes by proposing a substantial research project to test this hypothesis in the UK defence procurement situation.
Keywords: Defence sector; Monopolies; Relationship marketing; Transaction costs; United Kingdom